(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The experiment was carried out in the Old Brahmaputra Floodplain soil at the farmer’s field of Farming System Research and Development (FSRD) site, Kushumhati, Sherpur under Sherpur district in the medium high land under AEZ-9 for the three consecutive years 2003-06 to determine economic combined dose of organic and inorganic fertilizers for Potato-Boro-T.aman cropping pattern. Six treatment management packages including one farmer’s practices, and one fertilizer control were tested. The other four treatments were soil test based (STB) fertilizer dose for moderate and high yield goals (MYG and HYG), STB based fertilizer dose for HYG plus 5 t/ha cowdung (IPNS) and fertilizer dose for Fertilizer Recommendation Guide’97 (FRG ’97). Average of three years’ results showed that recommended fertilizer dose based on the FRG ’97 was more economic than all other fertilizer doses for the whole pattern. But the treatment Integrated Plant Nutrition Systems based on fertilizer management with cowdung for high yield goal produced the maximum grain and straw yields in the first crop. Application of cowdung had no significant effect on the yield of succeeding crops. The variable cost was higher for the treatment consisting of cowdung due to additional cost of cowdung. The highest marginal rate of return 1626% was obtained from recommended fertilizer based on the FRG ’97. Key Words: Balanced fertilization; cropping pattern; yield; economics DOI: 10.3329/bjar.v34i1.5751 Bangladesh J. Agril. Res. 34(1) : 41-49, March 2009